Development of a New Indirect ELISA Test for the Detection of Anti-Feline Coronavirus Antibodies in Cats - Irene Ferrero; Sarah Dewilde; Paolo Poletti; Barbara Canepa; Enrica Giachino; Paola Dall’Ara; Joel Filipe (Veterinary Sciences)
Background/Objectives: Feline coronavirus (FCoV) belongs to the family Coronaviridae and includes two pathotypes, the less virulent feline enteric coronavirus (FECV), which replicates in the enteric epithelial cells, and feline infectious peritonitis virus (FIPV), which is more virulent, replicates efficiently within monocytes/macrophages with systemic involvement and may cause feline infectious peritonitis (FIP), a progressive and often fatal disease. The diagnosis of FIP is complex and requires different examinations. Among serological tests, the indirect immunofluorescent antibody test (IFAT), considered the gold standard, and the enzyme-linked immunosorbent assay (ELISA) are the most widely used to detect FCoV antibodies. The aim of this work was the development of FCoVCHECK Ab ELISA, a new rapid indirect test for the detection of FCoV antibodies in feline serum/plasma samples. Methods: FCoVCHECK Ab ELISA was developed after a meticulous set-up and cut-off analysis through several methods, including the Youden’s index and ROC curve, to achieve the best test performance. It was validated by testing 110 feline sera (62 positives and 48 negatives) against the reference IFAT and compared with two other rapid ELISA tests, INgezim Corona Felino (Gold Standard Diagnostics) and ImmunoComb Feline Coronavirus (FCoV) [FIP] Antibody Test Kit (Biogal). Conclusions: FCoVCHECK Ab ELISA agreed with IFAT at 96.4% (93.5% sensitivity, 95% confidence interval (CI): 83.5–97.9%; 100% specificity, 95% CI: 90.8–100%), with ImmunoComb FCoV at 93.6% and with INgezim Corona Felino at 82.7%. Intra- and inter-assay accuracy and precision gave coefficients of variation lower than 20%. Compared to IFAT, the new assay correctly identifies positive and negative samples with a good correlation, and, in addition, it is simpler, faster and provides a less subjective reading of the results.